Efficacy and Safety of a Rapid Intravenous Injection of Ketamine 0.5 mg/kg in Treatment-Resistant Major Depression: An Open 4-Week Longitudinal Study. Issue 6 (December 2018) - Vidal, Sonia; Gex-Fabry, Marianne; Bancila, Victor; Michalopoulos, Giorgio; Warrot, Delphine; Jermann, Françoise; Dayer, Alexandre; Sterpenich, Virginie; Schwartz, Sophie; Vutskits, Laszlo; Khan, Nawaz; Aubry, Jean-Michel; et al.
Abstract: Background: Ketamine has been documented for its rapid antidepressant effects. However, optimal dose and delivery route have not yet been thoroughly investigated. The objectives of this study were to document the safety and test the antidepressant and antisuicidal effects of a single rapid 1-minute injection of ketamine 0.5 mg/kg in treatment-resistant depression (TRD). Methods: Ten patients with TRD were included in an open, noncontrolled 4-week study and received a rapid intravenous dose of ketamine 0.5 mg/kg. Main outcome measure was the Montgomery-Åsberg Depression Rating Scale and suicidality was assessed using the Scale for Suicide Ideation. Results: Rapid injection of ketamine elicited transient increase of blood pressure and altered states of consciousness in all patients and mild psychotomimetic effects in 4 patients, which all resolved without any intervention. Decrease of depression severity was observed from 40-minute postinjection until day 15. Eight patients became responders within 1 day and all were nonresponders after 4 weeks. The decrease of suicidal ideation was significant until day 7. Analysis indicated that higher severity of depression and anxiety at baseline predicted a larger Montgomery-Åsberg Depression Rating Scale decrease after 4 weeks. Conclusions: This study suggests that in well-controlled medical settings with adequate monitoring, a single rapid 1-minute injection of ketamine 0.5 mg/kg can be well tolerated and is efficacious in rapidly reducing depression symptoms and suicidal thoughts in outpatients with TRD. These findings are relevant to the practice of general clinical psychiatry and emergency departments were ketamine can have a place in acute management of TRD. Larger studies are necessary to confirm these results.